The art of successful business communication - Forsyth, Patrick (Institution of Engineering and Technology, 2008)
The following topics are dealt with: effective business communication; success prerequisites; business meetings; business presentation; negotiation; telephone communication; written communication; ubiquitous email; and other natures of business communication.